2010
DOI: 10.1016/j.marenvres.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage in trout erythrocyte in response to “in vitro” copper exposure

Abstract: 1The oxidative action of copper on different trout Oncorhynchus mykiss erythrocyte components was 2 studied. The results indicate that:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
(8 reference statements)
0
16
0
Order By: Relevance
“…In our study, an increase of TAC in plasma of fish fed the diet supplemented with PCE diet was observed. We analyzed the expression of genes coding for antioxidant enzymes in fish erythrocytes, as they have been previously used to monitor cellular oxidative stress response toward environmental and nutritional cues (Gwoździński et al ; Roche and Boge ; Fedeli et al , , Trenzado et al ). Erythrocytes transport oxygen in blood via a reversible association to hemoglobin, and as a result they are exposed to ROS and consequently to oxidative stress (Saltman ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, an increase of TAC in plasma of fish fed the diet supplemented with PCE diet was observed. We analyzed the expression of genes coding for antioxidant enzymes in fish erythrocytes, as they have been previously used to monitor cellular oxidative stress response toward environmental and nutritional cues (Gwoździński et al ; Roche and Boge ; Fedeli et al , , Trenzado et al ). Erythrocytes transport oxygen in blood via a reversible association to hemoglobin, and as a result they are exposed to ROS and consequently to oxidative stress (Saltman ).…”
Section: Discussionmentioning
confidence: 99%
“…TBARS value increased as a result of poor antioxidative capability. Fedeli et al () and Tang et al () reported that an excess of copper may increase the formation of ROS leading to damage of proteins, lipids and DNA. Higher values of TBARS were noted in H. fossilis fed diets containing lower and higher levels of copper than those who were fed optimum dietary copper, indicating that oxidative stress was induced in fish fed both copper‐deficient diet as well as diet having excess levels of copper.…”
Section: Discussionmentioning
confidence: 99%
“…Surfeit amount of copper can also lead to damage of cells and organs such as severe lesions on the intestine, liver, brain and gills (Berntssen, Hylland, Wendelaar Bonga, & Maage, 1999;Clearwater et al, 2002). Damage of proteins, lipids and DNA by reactive oxygen species is activated by copper ions and its complexes (Damasceno et al, 2016;Fedeli, Carloni, & Falcioni, 2010;Tang et al, 2017). Copper is also a vital component of the ceruloplasmin enzyme and plays important role in iron metabolism.…”
mentioning
confidence: 99%
“…Enhanced erythrocyte MNi frequencies were also observed in Channa punctata exposed to 0.4 mg/L copper for 24 to 168 h (Yadav and Trivedi 2009) and in the estuarine guppy Poecilia vivipara after a 96-h exposure to 9 mg/L Cu (Machado et al 2013). Finally, in vitro studies showed that incubation of rainbow trout (O. mykiss) gill homogenates with cooper resulted in altered DNA integrity by inducing single-and doublestranded DNA breaks (Arabi and Alaeddini 2005), though DNA damage was not observed in erythrocyte of this same species in response to copper exposure (Fedeli et al 2010). Taken altogether, these findings indicate that as related to lethality and the induction of MN, there is a differential sensitivity to Cu by different fish species and also a differential response to different metals in each fish species, with D. labrax being highly sensitive.…”
Section: Discussionmentioning
confidence: 99%